2012
DOI: 10.2105/ajph.2012.300773
|View full text |Cite
|
Sign up to set email alerts
|

The State of Research on Racial/Ethnic Discrimination in The Receipt of Health Care

Abstract: Objectives We conducted a review to examine current literature on the effects of interpersonal and institutional racism and discrimination occurring within health care settings on the health care received by racial/ethnic minority patients. Methods We searched the PsychNet, PubMed, and Scopus databases for articles on US populations published between January 1, 2008 and November 1, 2011. We used various combinations of the following search terms: discrimination, perceived discrimination, race, ethnicity, rac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
262
3
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 322 publications
(276 citation statements)
references
References 91 publications
7
262
3
2
Order By: Relevance
“…8 Most previous studies of discrimination in health care have examined the effects of patient race or ethnic back ground on treatment decisions. 9,10 These studies have typically presented physicians with clinical vignettes 11,12 or used observational databases and adjusted for confounding factors. 13 Far fewer studies have focused on discrimination on the basis of patient socioeconomic status.…”
Section: Discussionmentioning
confidence: 99%
“…8 Most previous studies of discrimination in health care have examined the effects of patient race or ethnic back ground on treatment decisions. 9,10 These studies have typically presented physicians with clinical vignettes 11,12 or used observational databases and adjusted for confounding factors. 13 Far fewer studies have focused on discrimination on the basis of patient socioeconomic status.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have investigated patients' perceptions of bias and discrimination while receiving health care. A review of this literature 55 found that up to 52% of blacks, 13% of Latinos, and 6% of nonHispanic whites have reported biased treatment based on their race or ethnicity. Perceptions of biased treatment in turn have been associated with reports of lower health, lower levels of self-care or adherence, interruptions in care, mistrust of clinicians, and underuse of available services, although some studies have not found these associations.…”
Section: Race/ethnicity Racism and Cvdmentioning
confidence: 99%
“…Not all bias is intentional, conscious or directed at the individual. 2 Discrimination research has emphasized that bias has a broader context that is not limited to interpersonal factors or encounters but also includes institutional, historic, and socially determined components with complex interplay in how individuals experience, internalize and react to bias. 3,4 As healthcare providers we want to believe that bias is not something we do and has led to the 'not-me-phenomenon,' referring to clinician beliefs that disparities do exist but not in their own clinical practices.…”
mentioning
confidence: 99%
“…Unfortunately, prior research has demonstrated that physicians do have unconscious beliefs and behaviors that influence the clinical encounter through communication, evaluation and treatment decisions with lasting effects on patient morbidity and mortality. [1][2][3] In this issue of JGIM, Pardies et al present an important contribution to the discrimination research literature by focusing on provider bias. 4 The article provides a thorough review between 1995 and 2012 including international studies, thus updating and expanding prior reviews.…”
mentioning
confidence: 99%
See 1 more Smart Citation